2021
DOI: 10.1002/mmce.22648
|View full text |Cite
|
Sign up to set email alerts
|

A single‐feed circularly polarized loop antenna using characteristic mode analysis

Abstract: A novel method for a single-feed circularly polarized (CP) loop antenna with both broad impedance bandwidth and axial ratio (AR) bandwidth is presented based on characteristic mode analysis (CMA). The circular polarization characteristics are generated by exciting two orthogonal degenerate modes (DMs) via single feeding simultaneously. The 90 phase difference is achieved by loading the lumped inductors or capacitors. The wide bandwidth characteristics are generated by splitting a pair of DMs. Consequently, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In summary, this subsection has reviewed the CMA of optimal antenna designs without MTS for CP radiation and improvement in AR. The optimal designs discussed above [55][56][57] demonstrate that CMA provides important information for CP performance and ARBW enhancement from CM parameters and current or field distribution. On the other hand, the designs described above illustrate how to optimize the feed position to provide CP radiation and improvement in ARBW from the modal current distribution.…”
Section: Cp Antennas Without Mtsmentioning
confidence: 99%
See 4 more Smart Citations
“…In summary, this subsection has reviewed the CMA of optimal antenna designs without MTS for CP radiation and improvement in AR. The optimal designs discussed above [55][56][57] demonstrate that CMA provides important information for CP performance and ARBW enhancement from CM parameters and current or field distribution. On the other hand, the designs described above illustrate how to optimize the feed position to provide CP radiation and improvement in ARBW from the modal current distribution.…”
Section: Cp Antennas Without Mtsmentioning
confidence: 99%
“…It has been observed that a square contour parallel dipole has shown a 90° phase difference for degenerating modes such as mode 2 and mode 3 by analyzing individual orthogonal current modes [52]. The designs discussed above have a low profile and can be fabricated easily [53][54][55][56][57][58][59]. However, some of those structures exhibit a narrow ARBW because the orthogonality and phase difference is achieved at a single frequency.…”
Section: Cp Antennas Without Mtsmentioning
confidence: 99%
See 3 more Smart Citations